2008
DOI: 10.1021/ol8011293
|View full text |Cite
|
Sign up to set email alerts
|

Biaryl Synthesis via Decarboxylative Pd-Catalyzed Reactions of Arenecarboxylic Acids and Diaryliodonium Triflates

Abstract: A novel simple and efficient synthesis of biaryls via a Pd-catalyzed decarboxylative cross-coupling reaction of arenecarboxylic acids and diaryliodonium triflates is described. The PdCl2/DPEphos catalytic system in the presence of Ag2CO3 in DMSO was found to be the most efficient. Various biaryls, including sterically hindered biaryls, were synthesized with yields ranging from 37 to 85%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(31 citation statements)
references
References 46 publications
1
28
0
2
Order By: Relevance
“…Using this method, a vast range of highly substituted, nonsymmetrical biaryls could be readily prepared (Scheme 25). [121] Scheme 21. a) Catalytic cycle for copper-catalyzed arylation and b) C3À C2 bond migration. …”
Section: Angewandte Chemiementioning
confidence: 99%
“…Using this method, a vast range of highly substituted, nonsymmetrical biaryls could be readily prepared (Scheme 25). [121] Scheme 21. a) Catalytic cycle for copper-catalyzed arylation and b) C3À C2 bond migration. …”
Section: Angewandte Chemiementioning
confidence: 99%
“…[18,21] Becht et al showed that the use of silver in overstoichiometric amounts is advantageous especially for methoxy-substituted arenecarboxylates. [22] Steglich, [23] Forgione and Bilodeau [24] discovered a different catalytic pathway for palladium-catalyzed decarboxylative crosscouplings, which is applicable specifically to five-ring heteroarenes bearing a carboxylate group in the 2-position. In their protocol, the carbopalladation presumably precedes the decarboxylation, so that the position of the carboxylate group is not the primary factor that defines the position of carbon À carbon bond formation.…”
Section: Introductionmentioning
confidence: 99%
“…在"第二代催化剂"的基础上, Goossen 课题组 [47,48] 分别实现了 Pd/Cu 催化邻/间/对位取代的羧酸脱羧与 ArOTf [47] 或 ArOTs [48] [56] , 使用 DPEphos 配体可以获得满意的反应产率. 此外, 三 价芳基碘盐具有稳定、易制备等优势 [57] .…”
Section: 脱羧 Heck 偶联反应unclassified